Psychopathology in siblings of children with pervasive developmental disorders [Yaygin gelişimsel bozukluǧu olan çocuklarin kardeşlerinde psikopatoloji] - (:unkn) unknown (My University, 2010)
Objective: In this article developmental and psychosocial adjustment problems observed in siblings of children with pervasive developmental disorders (PDD) are reviewed. For this purpose, medline was searched and books related with the subject and previous studies related with these siblings were examined. Results: Findings draw attention to the increase in the prevalence of PDD spectrum disorders and subthreshold problems which do not meet the diagnostic criteria for PDD in siblings of children with PDD. It has been reported that these siblings have delay and deviance in motor and language development. Although some studies have demonstrated that their adjustment are not different than controls, others draw attention to the increased risk they have for adjustment problems, high depression rates and especially for internalizing problems. Discussion: Because of the hereditary and psychosocial loadings they have, siblings of children with PDD are at risk for psychopathology. Psychiatric evaluation of the siblings in this context will make early diagnosis and intervention possible. The limited number of studies in this area, highlights the need for longutidunal follow-up studies which will be done with these siblings.
Keywords: Pervasive developmental disorders; Psychopathology; Risk; Siblings